Transformative Cyber Security Model for Malaysian Government Agencies - Perumal, Sundresan; Ali Pitchay, Sakinah; Narayana Samy, Ganthan; Shanmugam, Bharanidharan; Magalingam, Pritheega; Hasan Albakri, Sameer (International Journal of Engineering and Technology, 2018)
The growth of cyberspace world has uprising government agencies in a new way to serve citizen in a proactive, efficient and productive manner. To have an open, stable and vibrant cyberspace, governments should be more resilient to cyber-attacks and able to protect all government agency’s interest in cyberspace. Therefore, the government needs a transformative cyber governance security model to protect valuable government agencies’ information. The model should be able to detect, defend and deter the vulnerabilities, threats and risks that will emerge in the day to day government administration operation. This paper has introduced a study for some existing cyber governance security models. Thus, it helps in determining the main features of the required model.